PENGARUH GAME SMART SHAPE PADA BERPIKIR LOGIS ANAK USIA DINI - Mutiara; Ilhami, Akmillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effect of the “Smart Shape” game on the logical thinking abilities of children aged 5–6 years in TK Al-Kautsar Indralaya. A one-group pretest-posttest design was utilized with 16 participants. Children’s logical thinking skills were measured through an observation checklist covering four indicators: distinguishing, classifying, pattern recognition, and sequencing. The intervention involved playful learning activities using the Smart Shape game, and data were analyzed with a paired sample t-test. The results showed a significant improvement in logical thinking after the intervention. The percentage of children in the highest development category increased from 0% at pretest to 87.5% at posttest. Statistical analysis confirmed a significant difference between pretest and posttest scores (p < 0.05). These findings indicate that the Smart Shape game effectively enhances logical thinking abilities in early childhood and can be recommended as an innovative educational tool for teachers to engage children in fun, cognitively stimulating activities